Preparation and characterization of cephalexin loaded PLGA microspheres - Chaisri W. (2014)
The aim of this study was to evaluate the effects of emulsion type and process parameters on the properties of CPX-loaded PLGA microspheres in order to obtain delivery systems suitable for the treatment of dairy mastitis. The microsphere size was analyzed by photon correlation spectrophotometry. Determination of the drug loading was achieved by HPLC. It was found that CPX-loaded PLGA microspheres prepared using a w/o/w double emulsion technology were slightly larger (∼ 3-5 μm) but much higher in drug content (∼ 18 % w/w) than those obtained using o/w single emulsion preparation technology (average size was 2 μm, encapsulation efficiency was less than 2%). It was also demonstrated that stirring during emulsification and a change in both the internal and external phase of the emulsion, affected the size and the drug entrapment efficiency of the microspheres obtained. A 60/40 v/v mixture of chloroform and acetone was found to be the best organic solvent system for creating the primary emulsion. To obtain a high yield (>90%) of microspheres with a desirable size and high drug entrapment efficacy, a stirring rate of 8,000-10,000 rpm gave the best results. It is concluded CPX-loaded PLGA microspheres with suitable characteristics for the treatment of cows with dairy mastitis can be prepared by a w/o/w double emulsion preparation method. © 2009 Bentham Science Publishers Ltd.